2011
DOI: 10.1007/s12033-011-9429-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnaporthe oryzae Populations Adapted to Finger Millet and Rice Exhibit Distinctive Patterns of Genetic Diversity, Sexuality and Host Interaction

Abstract: In this study, host-specific forms of the blast pathogen Magnaporthe oryzae in sub-Saharan Africa (SSA) were characterised from distinct cropping locations using a combination of molecular and biological assays. Finger millet blast populations in East Africa revealed a continuous genetic variation pattern and lack of clonal lineages, with a wide range of haplotypes. M. oryzae populations lacked the grasshopper (grh) element (96%) and appeared distinct to those in Asia. An overall near equal distribution (47-53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 34 publications
3
43
0
Order By: Relevance
“…AFLP marker was also recognized here to be the most useful DNA fingerprinting tool for resolving the high genetic variation of this fungus compared with other fingerprinting techniques applied by several previous researchers such as RAPD and rep-PCR (6,15,(22)(23)(24). However, this research confirmed results obtained by JavanNikkhah (15) showing the low genetic variation among strains isolated from rice in Iran.…”
Section: Discussionsupporting
confidence: 81%
“…AFLP marker was also recognized here to be the most useful DNA fingerprinting tool for resolving the high genetic variation of this fungus compared with other fingerprinting techniques applied by several previous researchers such as RAPD and rep-PCR (6,15,(22)(23)(24). However, this research confirmed results obtained by JavanNikkhah (15) showing the low genetic variation among strains isolated from rice in Iran.…”
Section: Discussionsupporting
confidence: 81%
“…Similar results were obtained in Korea, when the analysis of 254 isolates demonstrated that all of them also belonged to MAT1-1 (Park, et al, 2008). In Africa studies revealed that 29% of isolates belongs to MAT1-1 and 71% to MAT2-2, but none of the isolates was hermaphrodite, avoiding crossing among them (Takan et al 2011). When two M. orizae populations from Himalayas were analyzed, it was found that 22% of the isolates belonged to MAT1-1 and 43% to MAT1-2, and isolates male fertile and hermaphrodite were detected, suggesting a possible occurrence of sexual recombination in this region (Kumar et al, 1999).…”
Section: Sexual Recombinationsupporting
confidence: 76%
“…On the Philippines, 1156 isolates were obtained on 38 cultivars sowed in two growing seasons and after analysis were grouped in only ten lineages (Chen et al, 1995). Simple population structure was also observed in Europe (Roumen et al, 1997) and Africa, when isolates from four different countries were separated in nine lineages (Takan et al, 2011). Results found in the literature reports a limited number of the pathogen lineages, showing a clonally typical population structure (Levy et al, 1993;Xia et al, 1993;Xia et al, 2000).…”
Section: Genetic Diversitymentioning
confidence: 90%
“…Node, neck, and stem tissues are also infected in addition to leaf sheaths. The blast pathogen infects several cereal crops, including rice, wheat, pearl millet, finger millet, and foxtail millet, and several grasses (12,13,21,26). The pathogen is variable but highly specialized in its host range.…”
mentioning
confidence: 99%